2006
DOI: 10.1038/sj.ki.5001861
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of fluid transport pathways and their determinants in peritoneal dialysis patients with ultrafiltration failure

Abstract: Ultrafiltration failure (UFF) is a serious complication of peritoneal dialysis (PD). The aim of the study was to analyze changes in water transport and their determinants in UFF patients over the time on PD. Standard peritoneal permeability analyses of 50 stable PD patients with UFF were analyzed. Fluid transport through small pores (SPT), free water transport (FWT) at 60 min, their contributions on total ultrafiltration (SPTC and FWTC), and their determinants were assessed. Patients were divided in Group I (U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
67
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 22 publications
14
67
2
Order By: Relevance
“…In addition, in the multivariate analysis of the peritonitis subgroups there was an association between membrane ultrafiltration capacity as well as PSTR in patients who had infections. Cause and effect cannot be inferred from this type of analysis, but this would be in line with more severe membrane injury causing reduced osmotic conductance and Pcl through more severe fibrosis (3,(20)(21)(22). This study's failure to detect a relationship between Pcl and comorbidity on multivariate analysis deserves comment.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, in the multivariate analysis of the peritonitis subgroups there was an association between membrane ultrafiltration capacity as well as PSTR in patients who had infections. Cause and effect cannot be inferred from this type of analysis, but this would be in line with more severe membrane injury causing reduced osmotic conductance and Pcl through more severe fibrosis (3,(20)(21)(22). This study's failure to detect a relationship between Pcl and comorbidity on multivariate analysis deserves comment.…”
Section: Discussionmentioning
confidence: 88%
“…This relative reduction in large-pore area could reflect many processes, including a resolution of the early inflammatory state of the membrane after the start of PD. Several studies have also shown that depending on when the initial membrane function tests are done, PSTR also decreases in the months after PD is established before the longer-term increase (10,(18)(19)(20)(21). Alternatively, it could mean that large pores are underrepresented in newly formed vessels (surprising because new vessel formation in diabetic nephropathy is associated with increased protein extravasation) or that interstitial and perivascular fibrosis, known to occur over time (1), is impeding large-pore leak through the interstitial structures.…”
Section: Discussionmentioning
confidence: 99%
“…Whether biochemical modifications of AQP1 (e.g. S-nitrosylation or abnormal glycation) may alter the integrity of the water pore and contribute to ultrafiltration failure remains unsolved (31,32). Similarly, the potential influence of variants in the AQP1 gene encoding AQP1 in the individual variability in free-water transport at the start of PD remains to be defined.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, overall, there is an increase, and not a reduction, in the abundance of AQP1 in the peritoneal membrane in typical ultrafiltration failure -as pointed in the detailed case study of Goffin et al (32). It is thus hypothesized that the interstitial fibrosis per se accounts for the reduction in transperitoneal UF, across both small and ultrasmall pores via a reduction in total LpS (31)(32)(33). One should stress, however, that mechanisms of ultrafiltration failure probably differ in shortvs.…”
Section: Aquaporin-1 In Ultrafiltration Failurementioning
confidence: 93%
See 1 more Smart Citation